Respostas
respondido por:
15
x = - b +/- √Δ dividido por 2 · a
Δ = b² - 4·a·c
Δ = 4² - 4·(-1)·(5)
Δ = 16 + 20 = 36
x = - ( 4) +/- √36 divido por 2 · a
x = - 4 +/- 6 divido por -2 ( o '' a'' é -1 )
x' = -4 + 6 divido por -2
x' = 2 divido por - 2 = -1
x'' = - 4 - 6 divido por -2
x''= -10 divido por -2 = 5
S = { X ? R / x< -1 ou x> 5 }
Δ = b² - 4·a·c
Δ = 4² - 4·(-1)·(5)
Δ = 16 + 20 = 36
x = - ( 4) +/- √36 divido por 2 · a
x = - 4 +/- 6 divido por -2 ( o '' a'' é -1 )
x' = -4 + 6 divido por -2
x' = 2 divido por - 2 = -1
x'' = - 4 - 6 divido por -2
x''= -10 divido por -2 = 5
S = { X ? R / x< -1 ou x> 5 }
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás